PENGARUH PEMANFAATAN LIMBAH KULIT SINGKONG DALAM PEMBUATAN PELET RANSUM UNGGAS - Sindu Akhadiarto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Cassava peels is one of agriculture waste having potency as feed for poultry. Cassava peels represent waste product from cassava industry with amount 1,998 million ton in the year 2006 in Indonesia (10 percentage of corm of yielded cassava). The weakness of cassava peels are low crude protein content, less palatable for ruminant and have voluminous characteristic. One of the effort to increase usefulness of cassava peels is by using cassava peels as fibre source in pellet complete ration for poultry. The aim of this research was to know best level from utilization of cassava peels as physic quality in poultry complete ration. This study used Completely Randomized Design that consistsof three treatments and three replications. The treatments were: 1). Control feeds + 0% cassava peels (R1), 2). Control feeds + 30% dry matter cassava peels (R2), 3). Control feeds + 30% boiling matter cassava peels (R3). Data was analysed with ANOVA and continued with Duncan Test. The result indicated that effect of water content pellet ration with moisture tool is higher than using infrared tool. Pellet rations with dry matter and boiling matter control treatment before saving have physic qualities that still meet the quality standar of poultry ration. Eventhough, on treatment after saving, the physic qualities decrease and relatively less meet the quality standar of poultry rationKey word: waste, cassava peels, poultry ration, pellet complete.